Assessment of pollution effect of direct use of poultry faecal waste in fish ponds (2006)
The performance of some environmental parameters in fish pond of 1.5ha at the National Institute For Freshwater Fisheries Research (NlFER) in New Bussa, Kainji dam resulting from the direct utilization of fresh poultry faecal waste as fish food was assessed along with three other ponds; South West Pond One (SWP1) using wheat offal, dough, maggot plus some poultry waste as fish feed and South West Pond Two (SWP2) using 100% concentrate, wheat offal and dough as fish feed. A Natural Water Pond (NWP) containing some fishes was also used as control pond along with SWPI and SWP2 to assess the pond at NIFER labeled Northern Pond ( NP). Environmental parameters of water quality in fish pond that are considered important in the assessment study are Dissolved Oxygen (DO); PH Value; Turbidity; Temperature, and 5-day Biological Oxygen Demand (BOD5). The temperature range is between 26-35C throughout the assessment work and this correspond with the optimum temperature for warm water fish growth. PH value of the study ponds fall within the excellent range. Also, turbidity in NP and SWP1 are very good thereby promoting effective ecosystem while SWP2 and NWP turbidity values are rather on the high side, hence photosynthesis is slightly affected. Dissolved Oxygen (DO) for the four ponds fall within 5-12 mg/l which is excellent for fish culture in ponds. BOD5 in the ponds is fairly high due to heavy manure loading with the exception of SWP2 which uses only concentrates as feed. NWP sources have the highest BODs value of 3.3 mg/l due to recharge from runoff water. From this assessment work it is evident that the direct utilization of poultry faecal waste as fish feed in fish ponds has great prospects if well monitored.